NILAI DEPLESI DAN DEGRADASI SUMBERDAYA ALAM DALAM PEREKONOMIAN KOTA KENDARI PROVINSI SULAWESI TENGGARA - Hasddin, Hasddin; Sukma Jaya, Fajar (EDUTECH CONSULTANT, 2019)
The problems and objectives studied in the study are to calculate the value of depletion and degradation of natural resources through the Green GRDP, to ensure that development continues while considering environmental principles as a basic aspect of measuring sustainability development. This study uses a quantitative descriptive approach. The main object analyzed in this study is economic performance in Kendari City GRDP in 2017 alone so that this study does not make a comparison or panel data (time series). Data were analyzed using Location Quotient (LQ) and Shift share analysis (SSA) equations which were then described qualitatively. The results of the study show that the value of GRDP (conventional) in Kendari City in 2017 is IDR 14,826,049.90 (million), where there are seven sectors as a base (LQ<1), namely Processing, Electricity, Gas and Water Industry; Construction; Trade, Hotels and Restaurants; Transportation and Communication; Finance; Rental and Corporate Services; and Services; while the rest (2 sectors) are non-base, namely the Agriculture sector and the Mining and Excavation sector (LQ>1). The value of depletion of natural resources (water) in GRDP is Rp. 548,313.3 (million). The highest depletion value occurs in the agricultural business sector / field, which is Rp. 410,204.2 (million), while the lowest is the processing industry, which is Rp 50.96 (million). The value of land degradation in the GRDP of Kendari City is IDR 2,212,389,105,000. This value is quite large because the existing critical land area reaches 26,735.82 ha. The semi-green GRDP value for 2017 is estimated at Rp 14,300,824.21, while the value of Kendari City Green GRDP in 2017 amounted to Rp 12,088,435.10 (million), meaning that the use of water resources and critical land in 2017 absorbs around 3.54% of the conventional GRDP of Kendari City.